Financial Technology Adoption: Network Externalities of Cashless Payments in Mexico. - Higgins, Sean (American Economic Review, 2024)
Do coordination failures constrain financial technology adoption? Exploiting the Mexican government's rollout of 1 million debit cards to poor households from 2009 to 2012, I examine responses on both sides of the market and find important spillovers and distributional impacts. On the supply side, small retail firms adopted point-of-sale terminals to accept card payments. On the demand side, this led to a 21 percent increase in other consumers' card adoption. The supply-side technology adoption response had positive effects on both richer consumers and small retail firms: richer consumers shifted 13 percent of their supermarket consumption to small retailers, whose sales and profits increased. (JEL E42, L25, L81, O14, O33)